Detection of Stator Winding Faults in PMSMs Based on Second Harmonics of Phase Instantaneous Reactive Powers - Shaopo Huang (Energies, 2022)
Reliable stator winding faults diagnosis is important for machine drives. This work presents an inter-turn short-circuit (ITSC) winding faults detection method for permanent magnet synchronous motors (PMSMs), based on the percentage of the second harmonics in phase instantaneous reactive powers (IRPs), defined in the abc frame of reference. In particular, the proposed indicator can locate the phase with ITSC for the PMSM with neutral conductor. The feature of ITSC in phase IRP is analyzed theoretically first, and a simulation setup is established in MATLAB/Simulink using the faulty PMSM model widely used for ITSC detection. From the theoretical analysis and the simulations, the second harmonic in phase IRP is proven to be the characteristic feature for fault detection. Simulations at different operating conditions show that the percentage of the second harmonic to its dc component in phase IRP, which is the proposed indicator in this article, is more reliable than the second harmonic amplitude itself for the ITSC detection and location. Experimental tests are carried out on a 3 kW motor with ITSC to investigate the effectiveness of the proposed indicator under different working conditions.